Comparative genomics analysis of pheophorbide a oxygenase (PAO) genes in eight pyrus genomes and their regulatory role in multiple stress responses in Chinese pear (Pyrus bretschneideri) - Ma, Yuchen; Sun, Jiao; Zhang, Xiao; Sadaqat, Muhammad; Tahir Ul Qamar, Muhammad; Liu, Tingting (Frontiers in Genetics, 2024)
Pyrus (pear) is among the most nutritious fruits and contains fibers that have great health benefits to humans. It is mostly cultivated in temperate regions globally and is highly subjected to biotic and abiotic stresses which affect its yield. Pheophorbide a oxygenase (PAO) is an essential component of the chlorophyll degradation system and contributes to the senescence of leaves. It is responsible for opening the pheophorbide a porphyrin macrocycle and forming the main fluorescent chlorophyll catabolite However, this gene family and its members have not been explored in Pyrus genomes. Here we report a pangenome-wide investigation has been conducted on eight Pyrus genomes: Cuiguan, Shanxi Duli, Zhongai 1, Nijisseiki, Yunhong No.1, d’Anjou, Bartlett v2.0, and Dangshansuli v.1.1. The phylogenetic history, their gene structure, conservation patterns of motifs, their distribution on chromosomes, and gene duplication are studied in detail which shows the intraspecific structural conservation as well as evolutionary patterns of Pyrus PAOs. Cis-elements, protein–protein interactions (PPI), and the Gene Ontology (GO) enrichment analyses show their potential biological functions. Furthermore, their expression in various tissues, fruit hardening conditions, and drought stress conditions is also studied. Based on phylogenetics, the identified PAOs were divided into four groups. The expansion of this gene family in Pyrus is caused by both tandem and segmental duplication. Moreover, positive and negative selection pressure equally directed the gene's duplication process. The Pyrus PAO genes were enriched in hormones-related, light, development, and stress-related elements. RNA-seq data analysis showed that PAOs have varied levels of expression under diseased and abiotic stress conditions. The 3D structures of PAOs are also predicted to get more insights into functional conservation. Our research can be used further to get a deeper knowledge of the PAO gene family in Pyrus and to guide future research on improving the genetic composition of Pyrus to enhance stress tolerance.